The effects of creamy and skimmed dairy products (milk, yoghurt and cheese) on lipid profile of healthy rats - Khalil, N. A.; Aly, S; Saad, M. A.; Sarbini, Shahrul R. (Rynnye Lyan Resources, 2024)
Milk and dairy products contain saturated fatty acids that have different effects on human health status and are risk factors for many diseases including cardiovascular disease and diabetes mellitus. The present study aimed to evaluate the impact of creamy and skimmed milk administration and certain dairy products (yoghurt and cheese) on healthy rats. A total of forty-nine healthy male Sprague Dawley rats were divided to seven groups. The treatment diet includes creamy and skimmed milk, creamy and skimmed yoghurt, creamy and skimmed cheese. After 60 days of consumption, body weight (BW) and lipids profile were measured. The final BW was higher in rats fed with creamy milk (256.40±23.81), and rats fed with creamy yoghurt (262.71±25.41) and creamy cheese (266.57±22.71). A significant elevation in the liver (aspartate aminotransferase and serum alanine) and kidney functions (urea, creatinine, and uric acid) have been observed in rats fed with fresh creamy whole milk and skimmed milk groups. The measured lipid profile has increased, especially rats fed with creamy milk, creamy, and skimmed cheese. In which, the total cholesterol has reached 159.70, 170.11 and 160.11. Meanwhile, the triglycerides increased to 125.51, 117.35 and 110.41. The low-density lipoprotein and the very low-density lipoprotein have also elevated with their atherogenic indexes at 5.2±0.55, 5.74±0.68 and 5.31±0.44 respectively. On the other hand, notable decreases were seen in the high-density lipoprotein cholesterol and liver glycogen compared to rats fed with control diet. In conclusion, both skimmed and creamy yoghurt indicated healthy nutritional properties, especially with lipid and atherogenic indexes by means of healthy liver and renal functions. Thus, yoghurt (creamy or skimmed) improved the healthy rats' lipid profile while creamy milk additions increased the BW. However, cheese (creamy or skimmed) is suggested to be avoided due to hyperlipidemic conditions in rats.